IRELAND’S SOUTH AFRICAN WAR 1899–1902 - Diver, Luke (Scientia Militaria - South African Journal of Military Studies, 2014)
It has been estimated that around fifty thousand Irishmen fought during the South African War, many of whom were at the forefront of a number of key engagements, serving in Ireland’s thirteen infantry battalions and three cavalry regiments. Ireland’s Imperial connections were further reinforced by the country’s impressive civilian contribution to the war effort. At least thirty-three militia battalions were mobilised during the course of the war, with seven units being despatched to the front, thirteen companies attested for the Imperial Yeomanry, many civilian Irish nurses and doctors enrolled into the army medical services, and tens of thousands of pounds were raised through various Irish war charities. Notwithstanding the immense Irish military contribution and contemporary civilian interest in the war, very little modern research or public knowledge exists on the subject. The dearth in research is perhaps due to Irish Nationalist historiography and sensitivity during the twentieth century, which has arguably distorted our perspective of Ireland’s shared history with the British Empire. Therefore, it is the purpose of this article to present an alternative Ireland, which has largely been ignored, by discussing Ireland’s military contribution and experience during the course of the war. In addition, the article attempts to recall the Irish public’s active demonstration of Imperial support and highlights the relationship that existed between Ireland and the British Empire during the conflict